The effectiveness of educational drama in the development of mathematical concepts in kindergarten (Journal of Hama University, 2020)
The present study aims to identify the effectiveness of educational drama in the development of mathematical concepts for the preparation of classrooms (60) children and girls between the ages of 5-6 years were distributed (30) experimental group and (30) control group, The results of the study were determined using the statistical program (spss) which confirmed the existence of differences between the experimental and control groups in the telemetry in favor of the experimental group. It also confirmed differences in the tribal and remote applications of the experimental group in favor of telemetry. The study concluded with a number of suggestions, the most important of which is activating the role of drama in kindergartens and taking advantage of its positive impact on the child to develop other skills of kindergarten children.